Transparência governamental, desigualdade de renda e desenvolvimento econômico do Ceará - Pereira, Márcio Aurélio Frota (2017)
This dissertation investigates the simultaneous relationship between economic development, institutional quality and income inequality, taking the municipalities of the state of Ceará as a reference. The connection between these endogenous phenomena is made from a large number of exogenous variables, which can be divided into groups, containing socioeconomic, institutional, financial and political characteristics. Using HDI for development, Gini index for inequality and municipal transparency index for institutional quality, the methodological basis is based on an econometric model of simultaneous equations applied to cross-section data of the municipalities of Ceará. The evidence points to a causal relationship between inequality and development. In turn, the institutional variable has explanatory relevance on development, however, this relevance was not verified on the inequality. On the other hand, development and inequality are significant in determining the level of transparency. In this sense, if the municipality has a high degree of transparency, its chances of being classified among the most developed grow 27.7%. Most of the exogenous variables were significant, with emphasis on the fiscal management index that positively impacts on transparency and negatively on income inequality. Municipalities with residents with higher average age and lower unemployment rate, end up reducing inequality. In addition, social capital and improved governance affect, respectively, positively and negatively transparency. In the context of the political variables, municipalities of re-elected mayors or those with a center or left ideology tend to reduce their transparency. In turn, increasing municipal transfers increases development.